The Arab Inequality Puzzle: The Role of Income Sources in Egypt and Tunisia - Caroline Krafft; Elizabeth E. Davis (Global Labor Organization (GLO), 2019)
Egypt and Tunisia are perceived to have high levels of inequality, yet based on standard measures, inequality in these two countries is not unusually high. In this study we explore a new dimension of inequality in Egypt and Tunisia by using a more complete measure of income and decomposing inequality by income sources (factor components). We find that higher-income households have more income sources than lower-income ones. Informal wage work and earnings from household enterprises are more common in Egypt than Tunisia, while formal wage work, pensions, and social assistance are more common in Tunisia. Social assistance does little to offset income inequality in either country. Enterprise earnings (in Egypt) and agricultural earnings (in Tunisia) as well as rent and other capital income in both countries play a large role in inequality. High inequality in these non-wage income sources may help explain why inequality is perceived to be high.
Keywords: D31; O15; P46; 330; Income inequality; inequality decomposition; wages; Egypt; Tunisia